Stroke prediction in patients presenting with isolated dizziness in the emergency department - June-sung Kim (Nature Portfolio, 2021)
Abstract Diagnosing stroke in patients experiencing dizziness without neurological deficits is challenging for physicians. The aim of this study was to evaluate the prevalence of acute stroke in patients who presented with isolated dizziness without neurological deficits at the emergency department (ED), and determine the relevant stroke predictors in this population. This was an observational, retrospective record review of consecutive 2215 adult patients presenting with dizziness at the ED between August 2019 and February 2020. Multivariate analysis was performed to identify risk factors for acute stroke. 1239 patients were enrolled and analyzed. Acute stroke was identified in 55 of 1239 patients (4.5%); most cases (96.3%) presented as ischemic stroke with frequent involvement (29.1%) of the cerebellum. In the multivariate analysis, the history of cerebrovascular injury (odds ratio [OR] 3.08 [95% confidence interval CI 1.24 to 7.67]) and an age of > 65 years (OR 3.01 [95% CI 1.33 to 6.83]) were the independent risk factors for predicting acute stroke. The combination of these two risks showed a higher specificity (94.26%) than that of each factor alone. High-risk patients, such as those aged over 65 years or with a history of cerebrovascular injury, may require further neuroimaging workup in the ED to rule out stroke.